2002
DOI: 10.1086/342717
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of RUNX2 Mutations in Japanese Patients with Cleidocranial Dysplasia Demonstrates Novel Genotype-Phenotype Correlations

Abstract: Cleidocranial dysplasia (CCD) is an autosomal dominant heritable skeletal disease caused by heterozygous mutations in the osteoblast-specific transcription factor RUNX2. We have performed mutational analysis of RUNX2 on 24 unrelated patients with CCD. In 17 patients, 16 distinct mutations were detected in the coding region of RUNX2: 4 frameshift, 3 nonsense, 6 missense, and 2 splicing mutations, in addition to 1 polymorphism. The missense mutations were all clustered within the Runt domain, and their protein p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
164
5
8

Year Published

2005
2005
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 136 publications
(199 citation statements)
references
References 61 publications
22
164
5
8
Order By: Relevance
“…The genotype-phenotype correlation regarding various RUNX2 mutations revealed that the Runx2 protein was differentially distributed between the nucleus and the cytosol in different mutants, demonstrating the importance of nuclear localization in bone development (48). This result suggests that the nuclear positioning of Runx2 in the nucleus promotes its transactivation activity, which provides an alternative molecular etiology for CCD development.…”
Section: Discussionmentioning
confidence: 87%
“…The genotype-phenotype correlation regarding various RUNX2 mutations revealed that the Runx2 protein was differentially distributed between the nucleus and the cytosol in different mutants, demonstrating the importance of nuclear localization in bone development (48). This result suggests that the nuclear positioning of Runx2 in the nucleus promotes its transactivation activity, which provides an alternative molecular etiology for CCD development.…”
Section: Discussionmentioning
confidence: 87%
“…4A). Interestingly, the T173I mutation was found in RUNX3 in the colon carcinoma cell line LS411, whereas its equivalent mutation in RUNX1 (T196I) was detected in chronic myelomonocytic leukemia (cancer.sanger.ac.uk/cosmic) (23)(24)(25); the equivalent residue in RUNX2 was found to be mutated, also to isoleucine, in the disease cleidocranial dysplasia (CCD) (26). This finding indicates that the T173 residue is important for the function of the Runt domain.…”
Section: Mutation Of T173 Results In Impairment Of Dna Binding and Trmentioning
confidence: 99%
“…In addition, a construct containing a point mutation within the RHD of TEL-AML1 was generated (MSCV-R201Q). R201Q is the most frequent mutation in the RHD of AML1 in human patients, found in familial platelet disorder with predisposition to AML (Song et al, 1999), AML (Preudhomme et al, 2000) and cleidocranial dysplasia (Quack et al, 1999;Zhou et al, 1999;Otto et al, 2002;Yoshida et al, 2002). Conservative mutation of this amino acid, at the corresponding position in mouse AML1 (R174), reduces the affinity of the AML1 RHD domain for DNA by 1000-fold, without disrupting heterodimerization with the corebinding factor (CBF)b cofactor or perturbing the RHD fold (Li et al, 2003).…”
Section: Expression Of Domain Deletion Mutants Of Tel-aml1 Using Retrmentioning
confidence: 99%